2004
DOI: 10.1007/s00059-004-2612-2
|View full text |Cite
|
Sign up to set email alerts
|

Neu initiierte Insulintherapie und kardiale autonome Funktion bei Typ-2-Diabetes

Abstract: The study demonstrates that insulin therapy with regular insulin optimizes cardiac autonomic function in type 2 diabetes mellitus. It emphasizes the value of cardiac reflex tests with regard to follow-up of cardiac autonomic function in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Schnell et al . 8 have reported that 4 months’ insulin therapy significantly shortened QTc in parallel with decreased HbA1c. The results are consistent with the finding of the present study that QTc was shortened following multiple daily insulin injections.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Schnell et al . 8 have reported that 4 months’ insulin therapy significantly shortened QTc in parallel with decreased HbA1c. The results are consistent with the finding of the present study that QTc was shortened following multiple daily insulin injections.…”
Section: Discussionmentioning
confidence: 98%
“…Two previous studies have evaluated changes in QTc in patients with T2D receiving insulin therapy, but these studies have not examined the correlation between the change in QTc and glycemic parameters. Schnell et al 8 have reported that 4 months' insulin therapy significantly shortened QTc in parallel with decreased HbA1c. The results are consistent with the finding of the present study that QTc was shortened following multiple daily insulin injections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations